Using biotechnology and genetic engineering to improve the quality and sustainability of plants and livestock - Nengsi, Sri Wahyu (Journal of Agro Complex Development Society, 2024)
Plants and livestock are essential sources of food for humans. However, crop and livestock productivity and health are often compromised by various factors such as pests, disease, drought, salinity, temperature extremes and pollution. Effective and sustainable breeding and conservation measures are needed to solve this problem. One option that can be used is biotechnology and genetic engineering. Biotechnology and genetic engineering are sciences that allow the genetic material of plants and livestock to be manipulated to obtain desired characteristics. This article discusses several examples of biotechnology and genetic engineering to improve quality and resistance in plants and livestock, such as transgenes, cloning, CRISPR-Cas9, gene editing and DNA synthesis. This article also discusses ethical, social, economic and environmental challenges and implications related to the application of biotechnology and genetic engineering in agriculture.